Legal Protection of Rohingya Citizens Related to The Conflict in Myanmar - Elfirda Ade Putri; Windy Sri Wahyuni; Muhammad Yusrizal Adi Syaputra; Agata Jacqueline Paramesvari; Gede Aditya Pratama (Universitas Negeri Gorontalo, 2023)
There are many crimes against humanity cases that occurred in the world. One of them is happened in Myanmar, which is Rohingya ethnic conflict. Rohingya ethnic conflict is an issue based on discrimination to Rohingya ethnic because there are some differences at ethnic and religion. Ethnic Rohingya is not recognized by Myanmar and not granted a status of citizenship Based on Myanmar Citizenship Law (Burma Citizenship Law 1982). This research was conducted to find out how the legal forms to Rohingya citizens based on international law. This methodology is a normative legal research that uses statutes, case, fact approaches. The research found that the role of UNHCR in handling Rohingya cases has been mandated by the United Nations and in accordance with UNHCR Statute. UNHCR plays an important role in addressing the issue of Rohingya case, at leas as initiator, facilitator, conciliator, and determination. Such roles were taken to resolve the conflict that face by Rohingya ethnic, like provide protection, safety, and facilitate every Rohingyas refugees needs. In addition to the role of UNHCR, some countries such as Indonesia, Thailand and Canada also provided some arrangement in addressing the issue of Rohingya.